Analysis of physicochemical characteristics of blood cell membranes of patients with rheumatoid arthritis - Puhteeva, Irina V.; Kaurova, Alesia V.; Gerasimovich, Natalya V.; Levin, Mark L.; Malkevich, Ludmila A. (Journal of the Belarusian State University. Ecology, 2022)
In the work reviewed and analyzed the results reflecting the physical and chemical state of the lymphocyte membranes of patients with rheumatoid arthritis. It was found that patients with rheumatoid arthritis did not show significant changes in the polarity of different areas of the membrane. At the same time discovered that annular lipid microviscosity of the plasma membrane of lymphocytes in patients with rheumatoid arthritis is reduced 2.5 times compared to control values in healthy patients, and the increased microviscosity in the general area of lipid bilayer was increased this by 25 % in relation to control values. The value of the degree of quenching of tryptophan fluorescence by pyrene in patients with rheumatoid arthritis is reduced by 35 % in relation to the control. In the membranes of red blood cells of patients with rheumatoid arthritis, there were no significant differences compared with the control values.